2009
DOI: 10.1177/0734242x08091865
|View full text |Cite
|
Sign up to set email alerts
|

Rotary drum composting of different organic waste mixtures

Abstract: The effects of three different mixtures of organic waste on composting in a rotary drum were examined by measuring changes in physico-chemical and biological parameters. It was observed that the time courses of the three mixtures: run A (grass cuttings, vegetable waste and food waste), run B (cattle manure, vegetable waste and sawdust) and run C (cattle manure, food waste, vegetable waste, paper waste and sawdust) were quite diverse. Run B, with initial C/N ratio 22 and containing a large proportion of cattle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 26 publications
(37 reference statements)
6
27
0
Order By: Relevance
“…In previous work, as well as in other authors experiences, elevated EC values were observed in compost made from dining wastes. This is associated to the presence of cellulosic material in the feedstock, such as napkins and tablecloths made with paper (Arrigoni et al, 2015;Faverial and Sierra, 2014;Kalamdhad and Kazmi, 2009a;Kalamdhad and Kazmi, 2009b). However, in this study, the differences in the EC values between the upper and the lower layers of the composter, also would show leachates accumulation in the lower part of the composter; leachates frequently include dissolved salts and, thus, increase compost electrical conductivity.…”
Section: Compost Stability Indicators and Quality Monitoring Variablesmentioning
confidence: 72%
See 1 more Smart Citation
“…In previous work, as well as in other authors experiences, elevated EC values were observed in compost made from dining wastes. This is associated to the presence of cellulosic material in the feedstock, such as napkins and tablecloths made with paper (Arrigoni et al, 2015;Faverial and Sierra, 2014;Kalamdhad and Kazmi, 2009a;Kalamdhad and Kazmi, 2009b). However, in this study, the differences in the EC values between the upper and the lower layers of the composter, also would show leachates accumulation in the lower part of the composter; leachates frequently include dissolved salts and, thus, increase compost electrical conductivity.…”
Section: Compost Stability Indicators and Quality Monitoring Variablesmentioning
confidence: 72%
“…Decentralized composting has been successfully implemented for kitchen and garden organic wastes treatment in institutions, neighborhoods and homes, at low costs (Platt et al, 2014;Smith and Jasim, 2009). Thus, this system represents an attractive technology alternative for the municipal organic waste fraction treatment in various socio-economic and technological contexts (Kalamdhad and Kazmi, 2009a;Kalamdhad and Kazmi, 2009b). Furthermore, small-scale composting is also an innovative way to involve generators as a key factor in their own waste treatment, raising community environmental awareness (Adhikari et al, 2010;Faverial and Sierra, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to literature, compost produced from catering waste, kitchen waste, or produced using home composters, has a wide variation on electrical conductivity (EC) values (from 1 to 10 dS. m -1 ) [2,34,35], but high soluble salt concentrations are more usually found in compost produced from cooked or preserved food [36]. Although, similar composed feedstock was equally incorporated into each composter, compost from AAC showed half EC values of those obtained from EVC and ATC; this could be attributed to a lower salt loss through lixiviation in these last two treatments prototypes.…”
Section: Resultsmentioning
confidence: 99%
“…YW used in this study had low initial moisture content of 35.63 ± 0.4% while FW recorded moisture content of 58.24 ± 0.4%. Optimum initial moisture content of raw feedstock ranges between 50 and 60% (Kalamdhad and Kazmi 2009). The analyses showed that YW and FW contained 17.17 ± 0.5% and 31.77 ± 0.5% of carbon, and 0.28 ± 0.2% and 3.43 ± 0.2% of nitrogen.…”
Section: Methodology Feedstock Materialsmentioning
confidence: 99%
“…The temperature inside the composter changed mainly due to heat generation as a result of degradation of organic matters by microorganisms and because of ambient air blown inside the composter for aeration purposes (Arslan Topal et al 2016). Greatest thermophilic activity would be observed during composting process when the temperature ranges between 52 and 60°C (Kalamdhad and Kazmi 2009;Mohee and Mudhoo 2005).…”
Section: In-vessel Compostermentioning
confidence: 99%